The meiobenthic communities of Senghor Seamount (Cabo Verde, tropical East Atlantic) - Kieneke, A.; George, K. H.; Trokhymchuk, R.R. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
Seamounts interest researchers because of their high biodiversity, high levels of endemism, and their importance for the dispersal and evolution of species. Especially interesting is the role of seamounts in the biogeography and phylogeography of interstitial meiofauna, microscopic animals that mostly lack dispersal stages in their life cycle. In this study, we analyse the composition of meiobenthic communities of the Senghor Seamount (Cabo Verde). The material was collected during the M79/3 cruise of R/V Meteor in 2009. Benthic sediments were collected with a multicorer and fixed with formaldehyde. Further extraction of meiofauna by density gradient centrifugation, sorting and counting of higher-level taxa was carried out in the laboratory. Our analyses involved estimating taxa densities, estimating different diversity indices and comparing similarity across sampling sites using non-metrical multidimensional scaling (nMDS). The results of the analyses showed that the summit has the highest higher taxa richness (HT: 11–16), the lowest level of dominance (D: 0.23–0.28), and the highest evenness of meiobenthic communities. The slopes had a lower level of higher taxa richness (HT: 12–13), a higher level of dominance (D: 0.5–0.61), and a lower level of evenness. The base had the lowest higher-taxon richness (HT: 10), the highest level of dominance (D: 0.82–0.87), and the lowest evenness. The nMDS revealed four distinct communities at the summit, the slope and the base of Senghor Seamount as well as at the deep-sea reference stations. There was a high dissimilarity of stations on the summit, which may indicate both, high biodiversity and heterogeneity of habitats. The slopes, the base and the reference sites show closer grouping of stations, which may indicate lower biodiversity of these areas, however, a lower number of stations were analysed. In comparison with other Atlantic seamounts and islands, Senghor Seamount shows up the second place regarding richness of meiobenthic higher-level taxa. The noticeably higher meiobenthic density values could be caused by the increased pelagic primary production in the sea area off tropical western Africa. Overall, the meiobenthic communities of Senghor Seamount seem to support the hypothesis of seamounts as oases for fauna, demonstrating more diverse assemblages compared to reference areas in the deep sea.